Experimental and computer simulation studies on badminton racquet strings - Suwannachote, N.; Imjai, T.; Wattanapanich, C.; Kefyalew, F.; Garcia, R.; Aosai, P. (Sensors, 2023)
This study investigates experimentally, numerically, and analytically the performance of different string materials (Kevlar, synthetic gut, natural gut, and polyester) on badminton racquets. Vibration and impact tests with a shuttlecock were performed using a racquet frame made of carbon graphite mixed with epoxy resin. Different string tensions were considered in the tests (20, 22, 24, 28, 30, and 34 lb), as well as different hitting locations on the racquet frame. The results show that, as the diameter of the strings increased, the elasticity of the string decreased from 0.529 to 0.447 for diameters ranging from 0.62 to 0.70 mm. Subsequently, a badminton racquet and shuttlecock were modeled using SolidWorks2018® software (version 26), and a maximum displacement was applied to the ball to simulate an impact on the string bed. The natural frequency, maximum deformation and maximum stress were calculated analytically, and a finite element analysis was also performed using ANSYS2022 R2® software (version 22.2). The analytical and numerical results from ANSYS® showed good agreement (within 5% accuracy). The results of the study show that the natural frequency of a racquet with Kevlar strings was significantly higher than that of racquets with synthetic gut, natural gut, or polyester string materials. Specifically, the natural frequency of a racquet made of carbon graphite and epoxy resin was 23.0%, 30.7%, and 36.2% higher than that of racquets with synthetic gut, natural gut, and polyester string material, respectively. On the basis of this finding, Kevlar was chosen as the preferred material for badminton racquets strings, and a parametric analysis was then conducted. The study showed that slightly lowering the tension of the off-centered strings had a minimal effect on the von Mises stress distribution of the ball and string bed. In addition to investigating string materials, this study also examined the effects of pull and diameter variations of racquet strings on vibrations during impact. This study contributes to the understanding of the role of racquet and strings in badminton, and it also provides new insights into the factors that can affect performance in the sport. By analyzing the performance of different string materials and examining the effects of pull and diameter variations of racquet strings, this study provides valuable information for players and manufacturers looking to optimize their equipment for maximum performance.